Investigating the potential of minocycline in reducing brain inflammation in chronic low back pain: a randomized, placebo-controlled mechanistic clinical trial - Mohammadian, Mehrbod; Morrissey, Erin J.; Knight, Paulina C.; Brusaferri, Ludovica; Kim, Minhae; Efthimiou, Nikolaos; Murphy, Jennifer P.; Alshelh, Zeynab; Grmek, Grace; Schnieders, Jack H.; Chane, Courtney A.; Sandström, Angelica; et al. (Pain (Amsterdam), 2025)
Supplemental Digital Content is Available in the Text.Minocycline, a tetracycline antibiotic, may neither reduce translocator protein positron emission tomography signal nor clinical pain in adults with chronic low back pain compared with a placebo comparator. AbstractOur group has shown that translocator protein (TSPO) levels, a putative marker of neuroinflammation, are increased in the brain and spinal cord of patients with chronic low back pain (cLBP). Whether neuroinflammation might be a therapeutic target for this condition is unknown. In this phase II double-blind, placebo-controlled, randomized clinical trial, we sought to evaluate whether the tetracycline antibiotic minocycline, which is commonly used as a glial inhibitor in preclinical models, has an effect on brain TSPO levels in adults with cLBP. Participants randomly received 100-mg minocycline or placebo, once a day for 2 weeks. The primary outcome was the change (pretreatment vs posttreatment) in thalamic TSPO levels, measured using [11C]PBR28 positron emission tomography signal (standardized uptake value ratio) and analyzed with a mixed effect model. Secondary outcome measures included the change in Brief Pain Inventory, severity subscore. Among 60 enrolled participants, 48 completed the trial. Of these, 25 received minocycline (age [years], mean ± SD: 44.6 ± 16.9; 9 female), and 23 received placebo (49 ± 17.1; 9 female). The mean thalamic positron emission tomography standard uptake value ratio was very stable across visits in both groups, with no significant group-by-time interaction (P = 0.956). Similarly, both groups demonstrated a comparable decrease over time in Brief Pain Inventory severity scores (P = 0.018) and no significant group-by-time interaction (P = 0.329). Our results suggest that minocycline, at the tested regimen, may neither reduce brain TSPO levels nor have clinically meaningful effects on clinical pain in patients with cLBP.